Thought Leadership: The Way Forward for the Malaysian Service Industry - Ying, Yeo Hui; Hee, Ong Choon (Current Aspects in Business, Economics and Finance Vol. 1, 2022)
It's worthwhile to have a more in-depth debate regarding the term's growing importance: thought leadership. It is advantageous to have a thought leadership culture. Thought leaders are trustworthy authorities who help individuals realize creative ideas by encouraging them. As time passes, thought leaders have a transformative impact on the industry, a certain specialty, or perhaps the entire world. Thought leadership is now not just possessed by individuals, but also by organizations. Some firms have been identified as thought leadership companies because they have adopted thought leadership qualities. Thought leadership differs from traditional leadership in several ways, including authority level, leadership style, information sharing, and problem-solving methods. When it comes to the Malaysian economy's major contributor, the services industry, there is a dearth of revolutionary and imaginative thought leaders. This emphasizes the importance of taking immediate action to cultivate thought leadership in the service business. There have also been suggestions for establishing thought leadership, such as distinguishing out among talent pools and catching the attention of industry experts. Hence, this study intends to identify the differences between thought leadership and traditional leadership and explore the ways how thought leadership can contribute towards the development of the Malaysian service industry. Several common mistakes that companies should prevent were also highlighted in this study such as copying others, lack of strategy, delivering low-quality content, misleading self-perception, and emphasis on self-promotion.